Pengembangan Bahan Ajar Berbasis Web untuk Meningkatkan Minat Belajar pada Mata Pelajaran Aqidah Akhlak - Nafilah, Anis Khofifatun; Mabnunah, Mabnunah; Zainab, Nurul (YASIN, 2023)
The purpose of this study is to create an online teaching resource for the course Aqidah Akhlak at MAN 1 Pamekasan and assess how students react to it. This study used the Research and Development (R&D) technique, with 30 students from MAN 1 Pamekasan in the eleventh grade serving as the research subjects. A student response survey serves as the study instrument, and descriptive qualitative analysis is used for data analysis. The findings of the study suggest that the generated web-based teaching materials have the ability to increase students' motivation for learning and improve their educational experiences. This is demonstrated by the favorable feedback that students have regarding the instructional materials, which feature adaptability, diverse subject matter, independence, social contact, and academic advantages. The development of online instructional materials for the topic of aqidah akhlak has shown to be a successful strategy for piqueing students' interest in the learning process. In addition to providing flexible access to the learning resources, this instructional material also gives students the tools they need to learn more independently. Additionally, a better overall learning experience is made possible by the social connections that the web platform fosters. The utilization of web-based teaching resources has enhanced Aqidah Akhlak learning at MAN 1 Pamekasan, according to the research findings.